Reflecting on the Impact of COVID-19 on Tourism in Italy - Singh, Akanksha; Sahu, Pooja (International Journal of Scientific Research and Management (IJSRM), 2022)
Italy was the first major western country to face the viral disease, which originated in China late last year and has spread around the world. Italian authorities have recorded some 2,29,858 confirmed cases and 32,785 death. Tourism is known as one of the most growing sector in Italy which is encouraging economic growth and development by giving employability of large sector of the working population. This paper is focusing on Coronavirus Disease (COVID-19) and its impact on Tourism Industry of Italy after a complete lockdown. In this paper we will come to know about popular tourist places in Italy and how they are affected after lockdown which has affected the economy of the country to a large extent. This paper also focused on why Italy was adversely affected due to Coronavirus and reasons behind it. Government has also taken various decisions for removal of COVID-19 and its impact on tourism industry of Italy.